East-West Design &Amp; Test Symposium (EWDTS 2013) 2013
DOI: 10.1109/ewdts.2013.6673211
|View full text |Cite
|
Sign up to set email alerts
|

Researching of mathematical models based on optimal control approaches for congestion control in telecommunication network

Abstract: The paper presents the flow-based models that were designed for solving dynamic queues balancing problem on the telecommunication network routers. Within the models the problem of queue balancing was reduced to solution of the linear and nonlinear programming optimization problems. By using flowbased models with varying degrees of accounting parameters of transmitted flows the research of the queue balancing process was performed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The analysis of known solutions [4,5,[10][11][12][13][14][15][16][17][18][19][20][21][22] has shown that the results of the solution of the Congestion Management problem are not related to the results of the Resource Allocation and Congestion Avoidance tasks. That is why, in order to reduce the computational complexity of the calculations of the optimization problems, their distributed solution was proposed within the framework of the two-step method ( fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of known solutions [4,5,[10][11][12][13][14][15][16][17][18][19][20][21][22] has shown that the results of the solution of the Congestion Management problem are not related to the results of the Resource Allocation and Congestion Avoidance tasks. That is why, in order to reduce the computational complexity of the calculations of the optimization problems, their distributed solution was proposed within the framework of the two-step method ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results obtained in [11,12,15, 2022], a method for planning and active queue management on the interfaces of telecommunication network routers with the successive solution of overload control optimization tasks, the allocation of bandwidth of the interface and prevention of overload [12] is proposed. The analysis of known solutions for the joint solution of the Congestion Management, Resource Allocation and Congestion Avoidance problems presented in [21,22] demonstrated that the results of the solution to the overload management problem are not related to the results of the solution of the problem of the allocation of bandwidth of the interface and prevention tasks overload.…”
Section: Queuing Planning Model On Interfaces Of Telecommunication Romentioning
confidence: 99%
See 1 more Smart Citation